2000
DOI: 10.2528/pier00041801
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Gyroelectric Waveguides

Abstract: Circular conducting waveguides filled with gyroelectric media are studied in this paper and the dyadic Green's functions in these

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…The theory of excitation of closed waveguides filled with gyrotropic media has received much careful study, and there are many accounts of it (see, e.g., [1,2] and references therein). Open gyrotropic waveguides surrounded by an isotropic outer medium have been discussed in [3].…”
Section: Eigenfunction Expansions Of Source-excited Electromagnetic Fmentioning
confidence: 99%
See 2 more Smart Citations
“…The theory of excitation of closed waveguides filled with gyrotropic media has received much careful study, and there are many accounts of it (see, e.g., [1,2] and references therein). Open gyrotropic waveguides surrounded by an isotropic outer medium have been discussed in [3].…”
Section: Eigenfunction Expansions Of Source-excited Electromagnetic Fmentioning
confidence: 99%
“…where R (1) m,α and R (2) m,α are certain constants. It can be shown that the total field yielded by summing (integrating) eigenwaves over the found values of q satisfies the radiation condition at infinity (r = (ρ 2 + z 2 ) 1/2 → ∞).…”
Section: Formulation Of the Problem And Basic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of excitation of closed waveguides filled with gyrotropic media has received much careful study, and there are many accounts of it (see, e.g., [11][12][13] and references therein). Open gyrotropic waveguides surrounded by an isotropic outer medium have been discussed in [10,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The electrodynamical models of waveguide with plasma and without external dielectric layer were used [26,27]. Liu et al analysed circular conducting waveguides, filled with the gyroelectric material, using dyadic Green's functions [28]. However the attenuation of the electromagnetic wave were not analysed in these papers.…”
Section: Introductionmentioning
confidence: 99%